Improved Microbial Safety of Direct Ozone-Depurated Shellstock Eastern Oysters (Crassostrea virginica) by Superchilled Storage - López Hernández, Karla; Pardío Sedas, Violeta; Rodríguez Dehaibes, Sóstenes; Suárez Valencia, Víctor; Rivas Mozo, Isaura; Martínez Herrera, David; Flores Primo, Argel; Uscanga Serrano, Roxana (Frontiers in Microbiology, 2018)
The effect of superchilled storage at -1°C on the microbial safety of oyster depurated with 0.2, 0.4, and 0.6 mg/L ozone was studied for 14 days. Fecal coliforms (4,100-16,000 MPN/100g), E. coli (1,500-3,650 MPN/100g), V. cholerae non-O1/non-O139 (13.0-102.0 MPN/g), and Salmonella spp. (2.270-3.035x103 CFU/g) were initially present in raw oysters. After 6 h depuration, fecal coliform counts decreased (P<0.05) to 300, 20 and 20 MPN/100g for 0.2, 0.4 and 0.6 mg/L treatments, while a 0.3 log decrease in control oysters was observed. Initial E. coli counts decreased (P<0.05) in oysters to 50, 20 and 20 MPN/100g for 0.2, 0.4 and 0.6 mg/L treatments, respectively. A 1 log reduction in Vibrio cholerae non-O1/non-139 levels were observed in 0.4 and 0.6 mg/L-treatments after 2 and 4 h depuration. Salmonella spp. was not detected in oyster samples after 6 h depuration in 0.4 and 0.6 mg/L-ozone treatments. Considering the bacterial loads after depuration, at the end of superchilled storage the 0.4 mg/L-ozonated oysters attained lower (P<0.05) fecal coliform levels (280 MPN/100 g) and E. coli counts in 0.4 and 0.6 mg/L-ozonated oysters (20 and 95 MPN/100 g, respectively). A 2-log decrease in V. cholerae non-O1/non-O139 levels on day 5 in 0.4 and 0.6 mg/L-ozonated oysters (<0.3 MPN/g) was attained. V. cholerae non-O1/non-O139 counts in control oysters decreased 1 log on day 9 of superchilled storage. Salmonella spp. was not detected in ozonated and superchilled stored oysters. Levels of fecal coliforms, E. coli, Salmonella spp., and V. cholerae non-O1/non-O139 in nonozone-depurated oyster samples were higher than in control, 0.4 and 0.6 mg/L ozonated oyster samples during superchilled storage. The cumulative mortality ratesafter 14 days of storage for superchilled oysters (22.2%) was higher (P<0.05) than 0.6 mg/L O3 (7.2%) and 0.4 mg/L O3 (5.8%) treatments, and control oysters (5.6%). pH values in control oysters decreased significantly (P<0.05) throughout the storage period but not in oysters of both ozone treatments, indicating no detrimental effects on oyster survival. The results of this study suggest that superchilled storage enables ozonated shellstock oysters (0.4 mg/L-6 h) stored for 9 days to be safe human consumption.